A flexible smart manufacturing system in mass personalization manufacturing model based on multi-module-platform, multi-virtual-unit, and multi-production-line. (September 2022) - Zhang, Xianyu; Ming, Xinguo; Bao, Yuguang
Highlights: A road map of flexible layout of production resources is proposed. A framework of flexible layout of production resources is proposed. Methods of flexible layout for production platform and virtual unit are developed. Theoretical model for optimization of flexible production line is developed. It has a certain reference value for industry and government. Abstract: Since the 21st century, with the gradual improvement of customers' living standards and autonomy, customers are increasingly pursuing personalized products. In order to adapt to this environment, enterprises implement mass personalization manufacturing model. This new manufacturing model needs a complex production system to support, which should adaptive flexible configuration according to the dynamic needs of customers. This configurable and rapid adjustment production system is a flexible smart manufacturing system. This paper studies the flexible layout and optimization of resources for flexible smart manufacturing system in mass personalization manufacturing model, and solves the flexible production preparation problem of sales order based on customer personalization. The main research contents include: flexible layout of production platform, flexible layout of virtual unit, flexible layout and optimization of production line and equipment. As the result of this research, the utilization rate of production layout space and equipment can be improved and the total production cost can be saved. At the same time, the system framework, model algorithm, method and theory studied in this paper have reference value for the research of flexible smart manufacturing system in a new manufacturing model facing mass personalization under the current adaptable industrial trend.